The innate immune system contributes to tissue‐engineered vascular graft performance. Issue 6 (20th February 2015) - Hibino, Narutoshi; Mejias, Dane; Pietris, Nicholas; Dean, Ethan; Yi, Tai; Best, Cameron; Shinoka, Toshiharu; Breuer, Christopher
ABSTRACT: The first clinical trial of tissue‐engineered vascular grafts (TEVGs) identified stenosis as the primary cause of graft failure. In this study, we aimed to elucidate the role of the host immune response in the development of stenosis using a murine model of TEVG implantation. We found that the C.B‐17 wild‐type (WT) mouse (control) undergoes a dramatic stenotic response, which is nearly completely abolished in the immunodeficient SCID/beige (bg) variant. SCID mice, which lack an adaptive immune system due to the absence of T and B lymphocytes, experienced rates of stenosis comparable to WT controls (average luminal diameter, WT: 0.071 ± 0.035 mm, SCID: 0.137 ± 0.032 mm, SCID/bg:0.804 ± 0.039 mm; P < 0.001). The bg mutation is characterized by NK cell and platelet dysfunction, and systemic treatment of WT mice with either NK cell‐neutralizing (anti‐NK 1.1 antibody) or antiplatelet (aspirin/Plavix [clopidogrel bisulfate]; Asp/Pla) therapy achieved nearly half the patency observed in the SCID/bg mouse (NK Ab: 0.356 ± 0.151 mm, Asp/Pla: 0.452 ± 0.130 mm). Scaffold implantation elicited a blunted immune response in SCID/bg mice, as demonstrated by macrophage number and mRNA expression of proinflammatory cytokines in TEVG explants. Implicating the initial innate immune response as a critical factor in graft stenosis may provide a strategy for prognosis and therapy of second‐generation TEVGs.—Hibino, N., Mejias, D., Pietris, N., Dean, E., Yi, T., Best, C., Shinoka, T., Breuer, C. The innate immune system contributes to tissue‐engineered vascular graft performance. FASEB J. 29, 2431‐2438 (2015). www.fasebj.org